KONSELING KONVERGENSI DAPAT MENGURANGI EFEK PORNOGRAFI SAAT PEMBELAJARAN JARAK JAUH (PJJ) DI MASA PANDEMI COVID 19 - Hari Utami Dewi (Madaris: Jurnal Guru Inovatif, 2022)
The rationale for this article is to want to help students avoid the effects of pornography from using smartphones or laptops which are used daily for Distance Learning (PJJ) during the covid 19 pandemic. Convergence counseling is the author’s innovation that belongs to the stream of integrative counseling. Aims to reduce pornographic behavior through convergence counseling. The method used is a case study of students accessing pornographic sites and engaging in virtual sex. The solution taken is to integrate contemporary counseling with religious counseling which is called convergence counseling. The results obtained indicate that the use of convergence counseling can reduce the effects of pornography during PJJ during the covid 19 pandemic, which leads to increased awareness and self-concept be more religious in implementing their behavior in everyday life, so that adjusments are created according to norms and values religion. Keyword: convergence counseling, the effects of pornography, distance learning in the pandemic covid 19